3D Electrospun scaffolds promote a cytotrophic phenotype of cultured primary astrocytes. (10th April 2014) - Lau, Chew L.; Kovacevic, Michelle; Tingleff, Tine S.; Forsythe, John S.; Cate, Holly S.; Merlo, Daniel; Cederfur, Cecilia; Maclean, Francesca L.; Parish, Clare L.; Horne, Malcolm K.; Nisbet, David R.; Beart, Philip M.
Abstract Astrocytes are a target for regenerative neurobiology because in brain injury their phenotype arbitrates brain integrity, neuronal death and subsequent repair and reconstruction. We explored the ability of 3D scaffolds to direct astrocytes into phenotypes with the potential to support neuronal survival. Poly‐ε‐caprolactone scaffolds were electrospun with random and aligned fibre orientations on which murine astrocytes were sub‐cultured and analysed at 4 and 12 DIV. Astrocytes survived, proliferated and migrated into scaffolds adopting 3D morphologies, mimicking in vivo stellated phenotypes. Cells on random poly‐ε‐caprolactone scaffolds grew as circular colonies extending processes deep within sub‐micron fibres, whereas astrocytes on aligned scaffolds exhibited rectangular colonies with processes following not only the direction of fibre alignment but also penetrating the scaffold. Cell viability was maintained over 12 DIV, and cytochemistry for F‐/G‐actin showed fewer stress fibres on bioscaffolds relative to 2D astrocytes. Reduced cytoskeletal stress was confirmed by the decreased expression of glial fibrillary acidic protein. PCR demonstrated up‐regulation of genes (excitatory amino acid transporter 2, brain‐derived neurotrophic factor and anti‐oxidant) reflecting healthy biologies of mature astrocytes in our extended culture protocol. This study illustrates the therapeutic potential of bioengineering strategies using 3D electrospun scaffolds which direct astrocytes into phenotypes supporting brain repair. <boxed-text content-type="graphic" id="jnc12702-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> Astrocytes exist in phenotypes with pro‐survival and destructive components, and their biology can be modulated by changing phenotype. Our findings demonstrate murine astrocytes adopt a healthy phenotype when cultured in 3D. Astrocytes proliferate and extend into poly‐ε‐caprolactone scaffolds displaying 3D stellated morphologies with reduced GFAP expression and actin stress fibres, plus a cytotrophic gene profile. Bioengineered 3D scaffolds have potential to direct inflammation to aid regenerative neurobiology.